Empty-Base Explanation - Kappes, Yannic (Philosophical Analysis, 2023)
Why does a dough rise? We might cite the presence of yeast as a reason why and explain the mechanism by which one brings about the other. This book investigates the idea of Empty-Base Explanation, in which a phenomenon is brought about by a mechanism alone, without help from any reasons why. Examples of concrete applications in metaphysics, epistemology, logic, and philosophical theology further explain the concept of this philosophical tool.